2021
DOI: 10.1108/jfp-06-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

A rapid evidence assessment of psychological treatment approaches for stalking behaviour

Abstract: Purpose This paper aims to provide practitioners with a brief but comprehensive review of the current evidence base for psychological treatment approaches used in the UK that may be useful for stalking therapies. Design/methodology/approach A rapid evidence assessment was conducted on papers (post the UK Protection from Harassment Act, 1997) that discuss treatments of stalking (with or without a conviction) and associated offences/disorders. Therapies reviewed were Acceptance and Commitment Therapy, Cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…A second rapid evidence assessment conducted by Leigh (2021) integrated all forms of evaluative studies, including case studies. Similarly, it was concluded that research into the psychological treatment of stalking and relevant underlying factors remains in its infancy (Birch et al , 2018; MacKenzie and James, 2011; Purcell and McEwan, 2018).…”
Section: Desistance Deterrence Factors and Stalkingmentioning
confidence: 99%
See 1 more Smart Citation
“…A second rapid evidence assessment conducted by Leigh (2021) integrated all forms of evaluative studies, including case studies. Similarly, it was concluded that research into the psychological treatment of stalking and relevant underlying factors remains in its infancy (Birch et al , 2018; MacKenzie and James, 2011; Purcell and McEwan, 2018).…”
Section: Desistance Deterrence Factors and Stalkingmentioning
confidence: 99%
“…Each person who stalks will engage in this behaviour in the context of their situation, personality and maladaptive coping modes; stalking results from an event or situation combined with a psychological vulnerability (Purcell and McEwan, 2018; Siepelmeyer and Ortiz‐Müller, 2020). The multifaceted nature of, and motivations for, stalking necessitates a multifaceted approach (Leigh, 2021). Without definitive direction from available research, we would agree that an evidence directed therapist approach to working with those who stalk is essential, applying best practice whilst engaging in case-specific evaluation of outcomes (Davies and Nagi, 2017).…”
Section: Some Conclusionmentioning
confidence: 99%